Health economic methodology illustrated with recent work on Chlamydia screening: the concept of extended dominance. Issue 2 (12th December 2007) - Postma, M J; de Vries, R; Welte, R; Edmunds, W J
Abstract : The health economic concepts of dominance were reviewed on the basis of two recently published cost-effectiveness analyses on screening for asymptomatic Chlamydia trachomatis, one in this journal. On the basis of dominance, some strategies may be deleted from the set options from which to choose. The two investigated studies were from the United Kingdom and The Netherlands. Both studies nicely illustrate situations of so-called extended dominance in practical decision making. Extended dominance is a theoretical topic in many health-economic text books but is only scarcely encountered in daily practice. Although the concept of extended dominance is theoretical in nature, a formal analysis and explanation may help show which options under consideration are not optimal from a strictly health-economic perspective; however, these options might still be attractive policy options for other reasons.